Strategi Pembelajaran Efektif di Era Digital melalui Direct Instruction pada Mata Kuliah Aransemen Paduan Suara - Ance Panggabean; Junita Batubara; Arsen Nahum Pasaribu; Romahulina Saragih (Grenek: Jurnal Seni Musik, 2025)
This study aims to assess the effectiveness of the Direct Instruction (DI) model as a learning method in improving students' abilities in the Choral Arrangement course in the digital era. This study aims to emphasize the importance of implementing the DI model in the context of modern learning that is rich in technology integration, especially in Semester 6 of the Music Arts Study Program, Faculty of Languages and Arts, HKBP Nommensen University, Academic Year 2024/2025. The method applied is descriptive qualitative with a case study approach. Data were obtained through observations of the learning process, interviews with students, and documentation of the results of arrangement assignments. The results of the analysis show that the DI model, with a structured and planned teaching approach, can improve students' conceptual understanding, technical skills, and creativity in creating choral arrangements. The use of digital technology such as music notation applications and online learning media also increases the effectiveness of this model. In addition, students showed a good response to the clarity of instructions, measurable learning steps, and increased motivation to learn. This study states that Direct Instruction is relevant and can be adapted to learning needs in the digital era, especially in the context of practice-based courses such as Choral Arrangement.